Roads & SDGs, tradeoffs and synergies: Learning from Brazil's Amazon in distinguishing frontiers - Alexander S. P. Pfaff; Juan Robalino; Eustaquio J. Reis; Robert Walker; Stephen Perz; William Laurance; Claudio Bohrer; Steven Aldrich; Eugenio Arima; Marcellus Caldas; Kathryn R. Kirby (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
To reduce SDG tradeoffs in infrastructure provision, and to inform searches for SDG synergies, the authors show that roads' impacts on Brazilian Amazon forests varied significantly across frontiers. Impacts varied predictably with prior development - prior roads and prior deforestation - and, further, in a pattern that suggests a potential synergy for roads between forests and urban growth. For multiple periods of roads investments, the authors estimate forest impacts for high, medium and low prior roads and deforestation. For each setting, census-tract observations are numerous. Results confirm predictions for this kind of frontier of a pattern not consistent with endogeneity, i.e., short-run forest impacts of new roads are: small for relatively high prior development; larger for medium prior development; and small for low prior development (for the latter setting, impacts in such isolated areas could rise over time, depending on interactions with conservation policies). These Amazonian results suggest 'SDG strategic' locations for infrastructure, an idea the authors note for other frontiers while highlighting major differences across frontiers and their SDG opportunities.
Keywords: O12; O13; H23; H41; Q23; Q24; Q56; 330; Deforestation; roads; infrastructure; climate change; biodiversity; Brazil; Amazon